2020
DOI: 10.1093/jbcr/iraa048
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Antimicrobial Agents Against Bacterial Isolates From Burn Wounds

Abstract: Abstract Topically applied antimicrobials are key to the prevention of infection and mortality in the acute burn population. The purpose of this study was to determine the in vitro effectiveness of commercially available topical antimicrobials, as well as topical preparations that were compounded in our burn care institution. One-hundred twenty microorganisms were tested against these topical antimicrobials and in vitro effectiveness was observed. Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In contrast to our results, in an in vitro study conducted on bacterial isolates from burn wounds, it was shown that MA had no effects on Gram-negative bacterial isolates. This might have been the result of its heavy use in burn units, fostering the generation of potentially resistant organisms [37]. Thus, the findings of our study remain limited, as PA isolated from wounds can exhibit specific resistances, which in turn can vary their susceptibility against PRT, CA, LAV and MA.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast to our results, in an in vitro study conducted on bacterial isolates from burn wounds, it was shown that MA had no effects on Gram-negative bacterial isolates. This might have been the result of its heavy use in burn units, fostering the generation of potentially resistant organisms [37]. Thus, the findings of our study remain limited, as PA isolated from wounds can exhibit specific resistances, which in turn can vary their susceptibility against PRT, CA, LAV and MA.…”
Section: Discussionmentioning
confidence: 87%
“…In an in vitro study of wound irrigation solutions containing SHC, LAV showed a relevant antimicrobial effect on PA of the six investigated solutions, while also showing a cytotoxic effect on keratinocytes and fibroblasts, depending on the treatment duration and concentration [28]. These cytotoxic effects are why LAV is not recommended to be used on grafts [37].…”
Section: Discussionmentioning
confidence: 99%
“…Burn patients' photographs are illustrated in Figures 1 and 2 on the admission of Groups I and II, respectively. The median age with the IQR was 24 (14,40) in Group-1 and 19 (12,60) months in Group-2. In Group-2, 21 (60%) were girls, whereas in Group-2, 15 (42.9%) were girls.…”
Section: Resultsmentioning
confidence: 95%
“…Mupirocin, an antibiotic produced from the fermentation process of Pseudomonas fluorescens , has also been highlighted as a powerful inhibitory effector against Gram-positive skin flora bacteria, such as coagulase-negative staphylococci and S. aureus , including MRSA [ 98 ]. Nystatin, an antibiotic produced from Streptomyces noursei , is considered a potent antifungal agent, whose action arises from its connection to the cell membrane sterols of fungi, imparting significant effects on wounds colonized by C. albicans [ 99 ]. Antiseptic agents such as povidone, cadexomer iodine, chlorhexidine, polyhexamethyl biguanide, and honey have also been applied to treat chronic wounds both to reduce inflammation and/or fight infections [ 17 ].…”
Section: Prevalent Skin Infections and The Biomolecules Employed In Their Treatmentmentioning
confidence: 99%